Heyde's syndrome: exploring the link between aortic stenosis and an acquired bleeding disorder. (18th April 2013) - Ledingham, David
Abstract : Heyde's syndrome was first proposed in 1958. It refers to gastrointestinal haemorrhage resulting from a combination of aortic stenosis with angiodysplasia. This report explores the case of a 93-year-old lady who was admitted to hospital following a neck of femur fracture. She suffered from multiple comorbidities including renal failure and congestive heart failure secondary to critical aortic stenosis. As an inpatient she suffered an exacerbation of both her heart and renal failure postoperatively. A week later she suffered from heavy upper gastro-intestinal bleeding, which failed to respond to pharmacological and endoscopic therapies as well as angiographic embolisation. The pathophysiology of Heyde's syndrome: an acquired von Willebrand deficiency syndrome has a much wider impact than was commonly thought, both in terms of how common it is and in how the association may be extrapolated to a wide range of bleeding disorders, rather than simply angiodysplasia associated gastrointestinal haemorrhage.